BANK SAYUR ORGANIK ALTERNATIF MENINGKATKAN KETAHANAN PANGAN RUMAH TANGGA DI DESA SETIAWARGI - Nurfadilah Siregar; Khomsatun Ni’mah; Dwi Apriyani; Iis Aisyah (LP4MK STKIP PGRI Lubuklinggau, 2022)
The fact that the village is the recipient of conditional social assistance for the poorest families in Tamansari District, Tasikmalaya City in 2019 is a component of great concern in Setiawargi Village. Food security, particularly during the current pandemic, is one of the issues associated with the community in the village. There is concern that this will further worsen the household food security situation, particularly for sustainable farming households. In Depok, Setiawargi Village, the alternative offered by external parties, namely the Siliwangi University Community Service Team through the Food Security Scheme, is to assist in the procurement of organic vegetable banks to target farming group partners and women's farming groups. The implementation activities to be carried out include: 1) observation of the community's initial needs; 2) preparation of seeds and post-observation equipment; (3) Home yard optimization counseling; (4) Introduction to organic vegetable banks; (5) Organic vegetable packaging, design, and marketing training; and (6) Organic vegetable planting assistance. The results of this activity suggest that the local community is passionate about the concept of an organic vegetable bank. The issue, however, is that the use of organic fertilizers has not been maximized so far because of the long-term results obtained. Other external parties, such as farm extension workers who work in synergy with the community service team, must continue to assist the local community to experience the minimal benefits of an organic vegetable bank for the welfare of the family, hoping to meet the needs of other communities in the future.